Impact of Clinical Characteristics and Treatment on Cholangiocarcinoma Prognosis in Southern Thailand - Chirawadee Sathitruangsak; Tanawat Pattarapuntakul; Apichat Kaewdech; Tortrakoon Thongkan; Apinya Prisutkul; Phatcharaporn Thongwatchara; Hutcha Sriplung; Chanon Kongkamol; Kanyanatt Kanokwiroon; Sumalee Obchoei; Pimsiri Sripongpun (Cancer Medicine)
ABSTRACT Background Cholangiocarcinoma (CCA) is most commonly seen in Northeastern Thailand and other parts of Asia where liver flukes are prevalent. However, it is unknown whether CCA patients in low and high liver fluke prevalence areas are similar. This study aimed to analyze the clinical characteristics and outcomes of CCA patients in Southern Thailand. Methods We retrospectively reviewed 223 patients diagnosed with CCA between 2018 and 2021 in a tertiary‐care center. Clinicopathologic data were reviewed and compared between intrahepatic, perihilar, and distal CCA (iCCA, pCCA, and dCCA, respectively). Overall survivals (OS) were determined by Kaplan–Meier method and multivariable Cox regressions. Results The mean age was 63.9 years; 50.7% were men. The most common subtype was iCCA (49.3%), followed by pCCA (36.3%) and dCCA (14.3%). Most patients were diagnosed at a later stage: 59.4% TMN stage IV and 23.3% stage III. Cirrhosis was present in 6.3%, while the presence of liver fluke was not detected. Only 15.1% of the cohort were deemed resectable. The median OS for iCCA, pCCA, and dCCA patients were 27.3, 22.0, and 19.3 weeks, respectively (p = 0.9). One‐year survival rate differed significantly between resectable and unresectable patients (85.2% vs. 21.2%, p < 0.0001). TMN stage (aHR 1.88), palliative biliary drainage (aHR 0.31), and systemic chemotherapy (aHR 0.19) were independent predictors for mortality in unresectable pCCA and dCCA patients. In unresectable iCCA patients, only systemic chemotherapy was significant (aHR 0.30). Conclusion Most patients were diagnosed late, and the median OS was only 5–6 months. Unresectable CCA patients with systemic chemotherapy and palliative biliary drainage had better survival rates.